The water-polo intermittent shuttle test: A match-fitness test for water-polo players - Mujika, I.; McFadden, G.; Hubbard, M.; Royal, K.; Hahn, A. (International Journal of Sports Physiology and Performance, 2006)
Purpose: To develop and validate an intermittent match-fitness test for water-polo players. Methods: Eight male junior players performed the Water Polo Intermittent Shuttle Test (WIST) twice to assess test reliability. To assess test sensitivity and validity, 104 male and female players from different competition standards and playing positions were tested. Eighteen players performed the WIST 5 times throughout a season to track fitness changes. Twelve players performed the WIST 48 hours before 4 consecutive National League games, and coaches awarded individual match-fitness scores based on game performances to assess the relationship between match fitness and test results. Heart rate (HR) and blood lactate (Lablood) were measured during and after each test, respectively. Results: Test-retest performance values were 216 ± 90 vs 229 ± 96 m (r = .98, P = .0001, coefficient of variation [CV] = 5.4%), peak HR 190 ± 8 vs 192 ± 10 bpm (r = .96, P = .0002, CV = 1.2%), and Lablood 7.0 ± 1.8 vs 6.4 ± 1.6 mmol/L (r = .84, P = .0092, CV = 8.8%). Significant differences were observed among different standards of play (range junior regional females 102 ± 10 m, senior international males 401 ± 30 m) and playing positions (field players 305 ± 154 m, center forwards 255 ± 118, goal keepers 203 ± 135 m). Test performance was lower in the early season (344 ± 118 m) than the remainder of the season (range 459 ± 138 to 550 ± 176 m). WIST performance and match-fitness scores correlated for all field players (r = .57, P = .054) but more highly for field players other than center forwards (r = .83, P = .0027). Conclusions: The WIST is a reliable, sensitive, and valid match-fitness test for water-polo players. It could become a useful tool to assess the effects of different interventions on match fitness.